Penyebaran Dan Karakteristik Habitat Jenis Rasamal (Altingia excelsa Noronha) di Taman Nasional Gunung Halimun Salak - Istomo Istomo; Putri Novita Sari (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Rasamala (Altingia excelsa Noronha) is one of the primary species in Halimun Salak Mountain National Park that grows in the lower mountain forests. In addition to the value of conservation, almost all parts of rasamala species can be utilized such as wood, leaves, fruit, and the canopy as a bird habitat. Information of natural distribution and habitat of rasamala are needed for conservation and cultivation purposes. The objectives of this research are to identify the distribution pattern and habitat characteristics of rasamala in Halimun Salak Mountain National Park. Research was done by make square plots with 30x30 m2 size that spread in the area of Halimun Montain 15 plots and Salak Mountain 15 plots. The analysis used morisita index to know the distribution pattern of rasamala and linear regression analysis to determine the influence of environmental factors. The result showed that distribution pattern of rasamala was clumped. Environmental factors that affect the existence of rasamala encompass altitude above sea level, slope, temperature, humidity, soil C-organic content, and N-total where the most influential factor is the N-total content of the soil. F test results on regression showed that the variables tested in Resort Cikaniki simultaneously had no significant effect on rasamala density, while the variables tested at Kawah Ratu Resort had significant effect on rasamala density